The complete mitochondrial genome of red-tailed laughingthrush (Garrulax milnei). Issue 2 (3rd July 2018) - Zhang, Lei; Xu, Dajie; Xia, Tian; Yang, Xiufeng; Sun, Guolei; Wei, Qinguo; Sha, Weilai; Zhang, Honghai
Abstract: In this study, the complete mitochondrial genome of Garrulax milnei was sequenced for the first time. This mitogenome is 17, 871bp in length and it contains 22 tRNA genes, 13 protein-coding genes, 2 rRNA genes, 1 control region and 1 extra pseudo-control region. The base composition of the mitochondrial genome is 29.7% A, 24.5% T, 14.2% G and 31.6% C. The phylogenetic analysis based on the 12 protein-coding genes (except for ND6 gene) showed that G. milnei clusters with other two species that belong to genus Garrulax .